2020
DOI: 10.1093/mnras/staa1552
|View full text |Cite
|
Sign up to set email alerts
|

The post-maximum behaviour of the changing-look Seyfert galaxy NGC 1566

Abstract: We present results of the long-term multi-wavelength study of optical, UV and X-ray variability of the nearby changing-look (CL) Seyfert NGC 1566 observed with the Swift Observatory and the MASTER Global Robotic Network from 2007 to 2019. We started spectral observations with South African Astronomical Observatory 1.9-m telescope soon after the brightening was discovered in July 2018 and present here the data for the interval between Aug. 2018 to Sep. 2019. This paper concentrates on the remarkable post-maximu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 69 publications
7
17
0
Order By: Relevance
“…Conversely, soft excess emission is observed at all epochs when the accretion rate is across a critical value of L bol /L Edd ∼ 0.01. This could be explained as due to a state change associated with the spectroscopic changing-look phenomenon (Oknyansky et al 2019(Oknyansky et al , 2020, similar to that observed in CL AGN Mrk 1018 (Parker et al 2019) and Mark 590 (Denney et al 2014). Our results are broadly consistent with the recent study by Jana et al (2021), confirming the variable soft excess emission and its dependence on the Eddington ratios.…”
Section: Implications On the Agn State Transition By The X-ray Spectr...supporting
confidence: 92%
“…Conversely, soft excess emission is observed at all epochs when the accretion rate is across a critical value of L bol /L Edd ∼ 0.01. This could be explained as due to a state change associated with the spectroscopic changing-look phenomenon (Oknyansky et al 2019(Oknyansky et al , 2020, similar to that observed in CL AGN Mrk 1018 (Parker et al 2019) and Mark 590 (Denney et al 2014). Our results are broadly consistent with the recent study by Jana et al (2021), confirming the variable soft excess emission and its dependence on the Eddington ratios.…”
Section: Implications On the Agn State Transition By The X-ray Spectr...supporting
confidence: 92%
“…NGC 1566 is a galaxy with a very well‐studied variable active nucleus; however, the spectral and photometric data have big gaps. The most intensive multiwave photometic observations were done during past years after discovery of a new reawakening (Cutri et al 2018; Ferrigno et al 2018; Grupe et al 2018a; Kuin et al 2018; Parker et al 2019) and new CL phase (see Oknyansky et al 2018; Oknyansky et al 2019b; Oknyansky et al 2020 and references there). During these few years, 2 CLs were discovered in the object: First happened in 2018 when object changed from Sy1.9 to Sy1.2 (Oknyansky et al 2019b, Paper I) and second one in 2019 when object changed back to the low state (Oknyansky et al 2020, Paper II).…”
Section: Introductionmentioning
confidence: 99%
“…The most intensive multiwave photometic observations were done during past years after discovery of a new reawakening (Cutri et al 2018; Ferrigno et al 2018; Grupe et al 2018a; Kuin et al 2018; Parker et al 2019) and new CL phase (see Oknyansky et al 2018; Oknyansky et al 2019b; Oknyansky et al 2020 and references there). During these few years, 2 CLs were discovered in the object: First happened in 2018 when object changed from Sy1.9 to Sy1.2 (Oknyansky et al 2019b, Paper I) and second one in 2019 when object changed back to the low state (Oknyansky et al 2020, Paper II). This happened about 60 years after previous CLs (Pastoriza & Gerola 1970; Quintana et al 1975a), but, taking into account too long gaps in the spectral coverage, some other possible CLs could well have been missed.…”
Section: Introductionmentioning
confidence: 99%
“…These investigations of NGC 1566 have long history (see e.g. references at da Silva, Steiner, & Menezes (2017); Oknyansky, Winkler, et al (2019); Oknyansky et al (2020); Parker et al (2019)). The NGC1566 is one of the brightest and nearest galaxies with AGN in the South Hemisphere.…”
Section: Introductionmentioning
confidence: 99%
“…NGC 1566 is a galaxy with a very well-studied variable active nucleus, however the spectral and photometric data have big gaps. The most intensive multiwave photometic observations were done during past years after discovery of a new reawakening (Cutri, Mainzer, Dyk, & Jiang, 2018;Ferrigno et al, 2018;Grupe, Komossa, & Schartel, 2018;Kuin et al, 2018;Parker et al, 2019) and new CL phase (see Oknyansky et al (2018); Oknyansky, Winkler, et al (2019); Oknyansky et al (2020) and references there). During these few years 2 CLs were discovered in the object: first happened in 2018 when object changed from Sy1.9 to Sy1.2 (Oknyansky, Winkler, et al (2019) = Paper I) and second one in 2019 when object changed back to the low state (Oknyansky et al (2020) = Paper II).…”
Section: Introductionmentioning
confidence: 99%